Results of the study on measurements of heavy metals concentrations in organs and tissues of livestock grazing on pastures around mining industry in gobi zone - B, Bayatogtokh; D, Delgermoron; S, Tsend-Ayush; G, Lkhamjav; S, Tserenchimed; P, Bolormaa (Mongolian Journal of Agricultural Sciences, 2019)
Level of the heavy metals was measured in tissue and blood samples from 19 cattle, 20 horse, 38 camel, 89 sheep and 102 goats in several mining areas such as Ulaanbadrakh soum (uranium mining) and Airag soum (spar mining) of Dornogovi province. In addition, level of the lead in the liver of sheep and goat samples from Zuunbayan soum of Dornogovi province was bit higher than same samples from other sampling areas. In the result, level of the copper was 814 ppm in the liver samples of sheep, 734 ppm in the liver samples of goat and they were and 2.5-4.0 fold higher than international permissible value. On the other hand, level of the cadmium was 352,789±122,64 mg/kg in kidney samples of horse, indicating that amount of these heavy metals were enough high to have toxicities in animals. Except for these results, level of heavy metals was not higher than international permissible value in plant and soil samples. Говийн бүсийн уул уурхайн хайгуул олборлолтын бүс орчимд бэлчээрлэж буй малын эд, эрхтэн дэх хүнд металлын агууламжийг тодорхойлсон судалгааны дүнгээс Хураангуй: Дорноговь аймгийн Улаанбадрах, Зүүнбаян сумын нутаг дэвсгэрт ураны хайгуул, туршилтын олборлолт явуулж буй бүс нутаг, Айраг сумын жоншны уурхайн олборлолтын бүс нутаг орчим бэлчээрлэж буй 89 хонь, 102 ямаа, 19 үхэр, 38 тэмээ, 20 адууны эд эрхтэн болон цусанд хүнд металлын (хар тугалга, зэс, кадми) агууламжийг тодорхойлов. Хар тугалга нь тархи болон бөөрийг маш хүндээр гэмтээдэг, ясыг зөөлрүүлдэг, төдийгүй хордолт нь үхэлд хүргэх аюултай бодис билээ. Маш удаан хугацаагаар энэ бодист өртөгдсөн хүүхэд төдийгүй томчуудын мэдрэлийн системийг гэмтээдэг, бага багаар хуримтлагдсаар хордлого үүсгэх, хүний мэдрэлийн эрхтэнд муугаар нөлөөлөх талтай. Хар тугалга нь хүний биед нөлөөлөх байдлаараа хортой бодисын ангилалд ордоггүй. Хөнөөлт бодист тооцогдоно. Иймд мал амьтны эд эрхтэнд агуулагдаж буй хар тугалга болон зэсийн агууламжийг дахин нарийн судлах шаардлагатай байна. Түлхүүр үг: Хар тугалга, зэс, Индукцэн холбоост плазм масс спектрометр.